Unprecedented geological and political stability? An analysis of a prospective geological high-level nuclear waste repository in South Australia based on stakeholder theory, risk perception and deliberative democracy - Pickett, William (2016)
This paper analyses the technical, commercial, institutional and socio-political (TCIS) issues of a controversial proposal to develop an international high level nuclear waste (HLW) repository in South Australia in order to answer the question; could South Australia legitimise an international geological nuclear waste repository? The framework for the analysis uniquely draws parallels between the social amplification of risk framework, stakeholder theory and the innovation literature. The analysis of secondary and primary interview transcripts – supplemented by other publically available data – illustrates how stakeholders have used influence tactics to shape their salience based on the TCIS uncertainties identified, and their ability to amplify or attenuate risks. The findings suggest that the technology does not yet have socio-political legitimacy, based on secondary stakeholder groups’ opposition and influence tactics. This affected the outcome of political decision making. Cognitive legitimacy was yet to be established because South Australia does not yet have the knowledge and expertise – nor a suitable regulator – to successfully develop a repository, and the economic assumptions have not yet gone through a rigorous conjecture-refutation approach. The paper then concludes with recommendations that could create the conditions for legitimisation in the future.